Study In Silico Combination of Eucheumma cottonii and Sargassum sp. Extract as The Inhibitor Pir-A Gene of Vibrio parahaemolyticus source AHPND: Combination of Eucheumma cottonii and Sargassum sp. Extract as The Inhibitor Pir-A Gene of Vibrio parahaemolyticus source AHPND - Maulita Abrilia; Yuni Kilawati; Rahmi Nurdiani (Department of Aquaculture, 2026)
Acute Hepatopancreatic Necrosis Disease (AHPND) is a disease in vaname shrimp (Litopenaeus vannamei) caused by PirA and PirB toxins in Vibrio parahaemolyticus bacteria. The active compounds found in the combination of Eucheuma cottonii and Sargassum sp. extracts have the potential to inhibit the PirA toxin protein produced by V. parahaemolyticus bacteria as an alternative to antibiotics. This study aims to predict the interaction between the PirA receptor protein in V. parahaemolyticus bacteria and the active compounds identified from the combination extract of E. cottonii and Sargassum sp. using molecular docking methods. The test results showed that the extract compounds met all ADME predictions, with the best binding affinity value of -6.8 kcal/mol for piperine. This result is similar to the binding affinity value of the antibiotic alpha-Apo-oxytetracycline. The lowest binding affinity value is 3.7 kcal/mol, which is possessed by the Triethanolamine compound. The interaction produced by the piperine compound with the PirA protein target consists of hydrogen bonds in the form of conventional hydrogen bonds and π-donor hydrogen bonds, similar to the antibiotic used as a comparison. The piperine compound also produces π-π stacked interactions, while antibiotics produce π-sigma interactions. The amino acid residues produced by Piperine are ARG39 and TYR110, while the amino acid residues in antibiotics are THR16 and THR24.